Analysis Of Consumer Interest Towards Use Of J&T Express Services In Kotaagung Tanggamus - Jodi Rakhmat Ramadhan; Hepiana Patmarina (Cita konsultindo, 2024)
The purpose of this study was to determine changes in consumer interest in J&T Express Kotaagung service companies and to determine the response of J&T Express companies to changes in consumer interest. The sample of this study consisted of 100 respondents obtained from the lemeshow formula. Data analysis techniques in this study used multiple linear tests, t tests, F tests, and coefficient of determination tests Based on the problems and processing of the research results, it is concluded that services have a positive and significant influence on the intention to buy J&T Kotaagung. This means that services affect consumer interest in using J&T Kotaagung shipping services. It is hoped that J&T Kotaagung will further improve the quality of services according to consumer expectations.